EVALUATING THE EFFECTIVENESS OF FLEXIBLE URETERORENOSCOPY COMBINED WITH LASER LITHOTRIPSY FOR THE TREATMENT OF MULTIPLE UNILATERAL INTRARENAL STONES SMALLER THAN 2 CM AT SECONDARY CARE HOSPITAL (The Research of Medical Science Review, 2024)
Urolithiasis, also known as urinary calculi, is a disease that forms stones anywhere in the urinary system. To determine the effectiveness of Flexible Ureterorenoscopy Combination with Laser Lithotripsy for Multiple Unilateral Intrarenal Stones Smaller Than 2 cm at a secondary care hospital in Karachi. This descriptive study was conducted in the Department of Urology at The Kidney Center in Karachi. Demographic data, including age, name, residence, height (measured on a stadiometer with light clothing and bare feet), weight (measured on a digital machine scale), and BMI (calculated as weight in kilograms divided by height in meters squared), were collected as part of the routine examination. The study included a total of 117 patients with a mean age of 45.3 years (±12.5), ranging from 18 to 65 years. Among the participants, 59.8% were male and 40.2% were female. The mean BMI was 28.4 kg/m² (±3.9), with 18.8% of patients classified as having a normal BMI, 38.5% as overweight, and 42.7% as obese. The mean stone size was 1.6 cm (±0.2), and the majority of stones were located in the renal pelvis (90.6%), with a smaller proportion in the renal calyces (9.4%). The success rates (SFR) varied according to stone size, with patients having stones smaller than 1.5 cm achieving a higher success rate of 92.5% (n=75), compared to those with stones in the 1.5–1.8 cm range, where the success rate was 85.4% (n=42). It is concluded that Flexible Ureterorenoscopy combined with Laser Lithotripsy is an effective and safe treatment for multiple unilateral intrarenal stones smaller than 2 cm, with a high stone-free rate and a low complication profile.